2016
DOI: 10.1016/j.ijid.2016.11.227
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prevalence, hepatitis B virus and hepatitis C virus among prison inmates, Chennai, India, 2015

Abstract: CDC) for surgical site infection surveillance. For the calculation of the numbers of operations per 100,000 inhabitants the Hungarian Central Statistics Office's yearly population data was used.Results: Beside the generally monitored categories, like Caesarean section, cholecystectomy, colon surgery and hip prosthesis (with 322.3, 240.7, 144.4 and 122.9 operations per 100000 per year), other, rarely under surveillance operations, frequency was high (herniorrhaphy, exploratory laparotomy, ovarian and breast su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…This study has found a 1.2% (95% CI = 0.0–2.4) prevalence of anti-HCV antibodies, and can be reported as very low, considering the prison population. 32 Our finding is in agreement with results reported in India (1.27%), 34 West Africa (0.5%), 37 and Turkey (0.5%) 17 but lower than results in Jimma (2.6%), Ethiopia. 27 Higher prevalence of HCV infection was reported in United States (10.1%), 43 Iranian (national data, 2015) (9.48%) 44 and Brazilian (5.3%) 19 prisoners.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study has found a 1.2% (95% CI = 0.0–2.4) prevalence of anti-HCV antibodies, and can be reported as very low, considering the prison population. 32 Our finding is in agreement with results reported in India (1.27%), 34 West Africa (0.5%), 37 and Turkey (0.5%) 17 but lower than results in Jimma (2.6%), Ethiopia. 27 Higher prevalence of HCV infection was reported in United States (10.1%), 43 Iranian (national data, 2015) (9.48%) 44 and Brazilian (5.3%) 19 prisoners.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the prevalence of HBsAg among prisoners was 6.5% (95% CI = 3.8–9.4); can be categorized as intermediate. 31 This result is in line with studies in Jimma, Ethiopia (5.8%), 27 India (3.89%), 34 Switzerland (5.9%), 35 and Iran (6.9%). 36 The prevalence in the present study is lower than studies conducted in Woldia prison, Ethiopia 10.4%, 28 West Africa 12.5%, 37 Nigeria 13.7%, 38 and Iran 18%.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the seroprevalence of HBV in the two study populations, differed significantly with in-mates having a higher seroprevalence than voluntary blood donors as shown in Table 3. These findings showed a higher seropositivity rate in the in-mates which are classified as high risk [13] compared to voluntary blood donors who are considered as low risk. This could be attributed to a higher risk of HBV transmission in prisons due to the lack of knowledge about HBV transmission modes [16].…”
Section: Discussionmentioning
confidence: 86%
“…Of the five articles [14][15][16][17][18] that were evaluated in our study, three were from New Delhi [14][15][16], one was from Tamil Nadu [17], and one was from Uttar Pradesh [18]. All studies were conducted using a crosssectional study design.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%